Perbedaan Kadar Kolesterol HDL pada Latihan Aerobik yang Diberikan Madu dan Tanpa Madu - Indardi, Nanang (Universitas Negeri Semarang, 2014)
The aimed to determine the effect of aerobic exercise run 2.4 km and supplemented honey 50 g of differences HDL cholesterol (High Density Lipoprotein). This study is an intervention study with RCTs (randomizedcontrolled clinical trials). A total of 30 male subjects were randomly selected from the Faculty of Sport Science students aged 18-23 years. Subjects were divided into 2 groups, treatment group 1 (n = 15) were given only aerobic exercise running 2.4 km; treatment group 2 (n = 15) were given aerobic exercise running 2.4 km and honey 50 g for 1 month, 3 times / week. To analyze differences in HDL cholesterol changes on two groups of Independent T test analysis was used. Results: There were significant differences in HDL cholesterol difference between the treatment groups (aerobic exercise running 2.4 km and supplemented honey 50 g) in the control group (aerobic training running 2.4 km). Conclusion: Aerobic exercise of running 2.4 km and effect supplemented honey for increasing on HDL cholesterol.